Ensino da leitura e escrita Braille no ensino remoto emergencial: desdobramentos da atuação docente - Soares, Kelly Guedes (2024)
The present study has as its main objective to describe the pedagogical practice in distance and face-to-face education for the teaching of reading and writing in Braille to students with blindness. With specific objectives: (a) characterize the pedagogical practice of the teacher of Special Education acting in the Specialized Educational Care (AEE) for the teaching of Braille reading and writing to students with blindness; (b) verify the reading and written Braille of students with blindness, in the perception of the regent teacher of regular education after remote education; and (c) check the impacts of remote learning on Braille read and writing of blind students, on the perceptions of the Regent teacher in regular education. A qualitative study, with a descriptive approach. Three special education teachers who work at the EEA and three regent teachers participated. The study was conducted in 3 public schools in the State of Amapá-AP. For data collection, a semi-structured screenplay of interviews was used for teachers working in the EEA, a semistruktured screenplay for interviews for regular school teachers and a sheet for characterization of profile and teaching performance. The data collected were analyzed and organized using the method of categorical content analysis. Three categories were evaluated and the following results were obtained: In the first category “Pedagogical practices in distance learning”, consensus was reached on the use of activities mediated by technologies and activities submitted through WhattApp. The resources used were rigging, punching and low-cost concrete and recyclable materials for refining and tactile discrimination activities. In the second category “Learning reading and writing by blind students in distance learning”, it was possible to note that students with blindness learned the Braille system, requiring more support to reach the rest of the class in the acquisition of dynamic reading and fluent writing. The third category, “Effects of remote learning on Braille reading and writing of the student with blindness”, was consensus, due to the delay in literacy process; the shutdown that suspended remote classes and brought more damage to the schooling of students of the early years of primary school. The efforts made by the teachers to encourage the participation and learning of students with blindness are undeniable. The data showed that early training is crucial for teaching performance and for the inclusion of students with blindness. The limitations of the study include, sample size and time restrictions for collecting information from a participant who has been recontaminated by COVID-19. The study's contributions focus crucial aspects for Braille reading and writing teaching, the pedagogical practices of Special Education teachers and educational studies related to the pandemic period of COVID-19 in the Amapaense scene. Keywords: Special Education. Distance learning. Visual impiamente. Braille reading and writing